2015
DOI: 10.1038/bjc.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Combining bevacizumab and chemoradiation in rectal cancer. Translational results of the AXEBeam trial

Abstract: Background:This study characterises molecular effect of bevacizumab, and explores the relation of molecular and genetic markers with response to bevacizumab combined with chemoradiotherapy (CRT).Methods:From a subset of 59 patients of 84 rectal cancer patients included in a phase II study combining bevacizumab with CRT, tumour and blood samples were collected before and during treatment, offering the possibility to evaluate changes induced by one dose of bevacizumab. We performed cDNA microarrays, stains for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 73 publications
2
34
0
Order By: Relevance
“…Nonetheless, we reasoned that HRBC patients with baseline MVD greater than or equal to that of TNBC patients with pCR might follow a pattern similar to that of TNBC patients. Of note, this high MVD threshold in HRBC is lower than the lowest MVD of all patients assessed in a recent colorectal study (27). In this descriptive analysis of high baseline tumor MVD in the HRBC cohort, the majority of patients with a good response in the primary tumor after combination therapy (MP >3) had maintained or increased PC-MVD (Table S8 and Fig.…”
Section: Low Vascularity Poorly Perfusedmentioning
confidence: 68%
See 1 more Smart Citation
“…Nonetheless, we reasoned that HRBC patients with baseline MVD greater than or equal to that of TNBC patients with pCR might follow a pattern similar to that of TNBC patients. Of note, this high MVD threshold in HRBC is lower than the lowest MVD of all patients assessed in a recent colorectal study (27). In this descriptive analysis of high baseline tumor MVD in the HRBC cohort, the majority of patients with a good response in the primary tumor after combination therapy (MP >3) had maintained or increased PC-MVD (Table S8 and Fig.…”
Section: Low Vascularity Poorly Perfusedmentioning
confidence: 68%
“…A phase II trial in 20 BC patients also noted an association between expression of the endothelial cell marker CD31 and tumor regression (23). In patients with other tumor types treated with bevacizumab and cytotoxic therapy, correlations between baseline MVD and response have also been documented (24,25), whereas other studies have found no relationship between MVD or MVD surrogates and response (26,27). The exploratory nature of our current analysis notwithstanding, the association between MVD and tumor regression scores is consistent with the notion that vascular remodeling postbevacizumab can convert some nonfunctional vessels into functional ones, but it cannot create new vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we assessed subtyping robustness in a meta‐analysis of publicly available rectal cancer biopsy datasets. We also performed temporal/spatial assessment of the stability of these classifiers, using both patient‐matched serial biopsies collected over a 3‐week period from the phase II AXEBeam study and multi‐region‐of‐origin colon biopsies from the Biopsies of Surgical Specimens (BOSS) study . Finally, as part of the S:CORT (Stratification in COloRecTal cancer) research programme , we assessed the ability of CRISs and CMSs to classify histologically‐diverse rectal biopsy samples from the phase II COPERNICUS study.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The PK data of mAb drugs are usually obtained using ELISA, which is sensitive to outside interference. 4,5 However, the details of assay validations were oen unavailable in those publications since the assay validations were usually not the key point in those studies, and there were few detailed reports about the interference of the edge effect on detection results. For this reason, controlling the edge effect will be valuable for improving the accuracy and precision of ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…2 mL blood was collected from the foreleg vein into heparinized centrifuge tubes, before and at 0.083, 2, 6, 12 h, 1,3,5,7,9,11,14,17,21,25,29,33,34,35,38,45,52,59, and 66 d aer administration. 2 mL blood was collected from the foreleg vein into heparinized centrifuge tubes, before and at 0.083, 2, 6, 12 h, 1,3,5,7,9,11,14,17,21,25,29,33,34,35,38,45,52,59, and 66 d aer administration.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%